2001
DOI: 10.2337/diabetes.50.12.2709
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Streptozocin Diabetes and Diabetes Treatment by Islet Transplantation on In Vivo Insulin Signaling in Rat Heart

Abstract: The insulin signaling cascade was investigated in rat myocardium in vivo in the presence of streptozocin (STZ)-induced diabetes and after diabetes treatment by islet transplantation under the kidney capsule. The levels of insulin-stimulated tyrosine phosphorylation of the insulin receptor ␤-subunit, insulin receptor substrate (IRS)-2, and p52Shc were increased in diabetic compared with control heart, whereas tyrosine phosphorylation of IRS-1 was unchanged. The amount of the p85 subunit of phosphatidylinositol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
34
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 65 publications
13
34
0
Order By: Relevance
“…As shown in our study, the insulin binding capacity of the receptors in the skeletal muscles of STZ diabetic rats significantly increases due to the increase in receptor number with high and low affinity to the hormone (Table 1). Our data concerning the characteristics of insulin receptor are in agreement with that obtained by the same method in rat skeletal muscles [23,24]. It allows us to conclude that functional disturbance in insulin-competent ACSM should not be ascribed to the decreasing of insulin receptor activity.…”
Section: Experimental Streptozotocin (Stz) Diabetessupporting
confidence: 80%
See 1 more Smart Citation
“…As shown in our study, the insulin binding capacity of the receptors in the skeletal muscles of STZ diabetic rats significantly increases due to the increase in receptor number with high and low affinity to the hormone (Table 1). Our data concerning the characteristics of insulin receptor are in agreement with that obtained by the same method in rat skeletal muscles [23,24]. It allows us to conclude that functional disturbance in insulin-competent ACSM should not be ascribed to the decreasing of insulin receptor activity.…”
Section: Experimental Streptozotocin (Stz) Diabetessupporting
confidence: 80%
“…The functional changes in the insulin signaling system we found in the skeletal muscles of STZ diabetic rats are similar to that in the myocardium of these animals [24,28,32]. In particular, in the myocardium of diabetic rats, the following events were observed: an increase in insulin receptor number, increase in insulin-induced phosphorylation of insulin receptor and its substrates (IRS1-and IRS2-proteins), and stimulation of PI-3K activity.…”
Section: Discussionsupporting
confidence: 48%
“…However, GSK3 activity was elevated approximately twofold in skeletal muscle samples from human patients with type 2 diabetes [128]. There was also decreased insulin-induced serine-phosphorylation of GSK3 in the myocardium of diabetic rats [129]. Thus, while still few, these studies indicate that the effects of insulin-resistance on GSK3 vary considerably among different tissues with some evidence of dephosphorylated, hyperactive GSK3 associated with insulin deficiency.…”
Section: Diabetes and Gsk3mentioning
confidence: 84%
“…In the myocardium of STZ-diabetic rats, systenic insulin administration results in an enhanced activity of most of the components of the PI3-K/ Akt signaling cascade, including an increase in Akt phosphorylation (Laviola et al, 2001). However, baseline Akt phosphorylation of serine-473, although not of threonine-308, and Akt activity (as determined by in vitro assay) showed reductions in STZ-diabetic rats (Laviola et al, 2001). Gerhardinger and coworkers (Gerhardinger et al, 2001) found that STZ-diabetic rats given low-dose insulin treatment tended to exhibit enhanced retinal Akt phosphorylation.…”
Section: Pi3-k/akt Pathway and Endothelial Dysfunction In Type I Diabmentioning
confidence: 99%
“…Indeed, STZ-induced diabetic rats demonstrate baseline reductions in cardiac Akt activity (Dobrzynski et al, 2002). In the myocardium of STZ-diabetic rats, systenic insulin administration results in an enhanced activity of most of the components of the PI3-K/ Akt signaling cascade, including an increase in Akt phosphorylation (Laviola et al, 2001). However, baseline Akt phosphorylation of serine-473, although not of threonine-308, and Akt activity (as determined by in vitro assay) showed reductions in STZ-diabetic rats (Laviola et al, 2001).…”
Section: Pi3-k/akt Pathway and Endothelial Dysfunction In Type I Diabmentioning
confidence: 99%